The Relationship Between Parent-Adolescent Communication and Adolescents' Self-Protection Skills Against Sexual Violence in Medan City - Afrila Syahrani; Dewi Elizadiani Suza (Universitas Prima Indonesia, 2025)
Sexual violence is a forced sexual act without consent and has consequences for health problems, namely reproductive health, physical health, and mental health, which can be felt in the short and long term. It has become a global issue that requires immediate attention. This study aims to analyze the relationship between parent-adolescent communication and adolescents' ability to protect themselves against sexual violence in Medan City. The research employs a quantitative approach using a descriptive correlation method, involving 52 respondents-students in grades X and XI at MAS Al-Jamiyatul Washliyah school in Medan City-selected through purposive sampling. The Chi-Square test was utilized for data analysis. Research data collection was carried out by distributing questionnaires using the google form application in May 2024, and computerized data processing using SPSS with univariate and bivariate data analysis. The findings revealed that 73.1% of respondents exhibited good parent-adolescent communication, 98.1% demonstrated effective self-protection skills, and 94.2% were considered at low risk of sexual violence. The results of the Chi-Square test indicated a significant relationship between parent-adolescent communication and the incidence of sexual violence, with a p-value of 0.003 (α = 0.05). However, there was no significant relationship found between adolescents' self-protection skills and the risk of sexual violence, as indicated by a p-value of 0.803 (α = 0.05). In conclusion, both parent-adolescent communication and self-protection skills are essential preventive measures against sexual violence. It is expected that schools can provide education related to the importance of parent-adolescent communication to prevent sexual violence.